Regulated the electrokinetic application of different plant growth stages and parameters enhance the economic extraction of soil heavy metals - Ma, Hongyan; Zhao, Ming; Yang, Na; Feng, Linhui; Wang, Lirong; Jiang, Chen; Jiang, Ming; Guo, Jianfang; Li, Tianguo (Frontiers in Plant Science, 2025)
IntroductionElectrokinetic-assisted phytoremediation (EKAPR) improved the heavy metal accumulation has been extensively covered, but the uneconomic of heavy metal extraction increment unit energy consumption (EHME) limits its development.MethodsThe feasibility from the dual perspectives of regulated the electrokinetics application of different growth stages of Sedum plumbizincicola and electrochemical parameters affecting power consumption to enhance the EHME of EKAPR system were investigated.ResultsResults shown that electrokinetic promoted heavy metals accumulation of S. plumbizincicola significantly, and it not show positive correlation absolutely with the application time. EK-B treatment exhibited high performance for Cu and Pb. Although the Cd and Zn extraction decreased 9.02%-15.63% for EK-B and EK-S compare with EK-W treatment due to difference in biomass, there was insignificant in the content. Comprehensive consideration of growth and accumulate characteristics, electrokinetic application in the booming stage (0.70 of PCA score) was alternative to replace whole growth period treatment. Orthogonal experiments results showed that four factors were insignificant with biomass, heavy metal content and extraction, while voltage gradients and application time had significant effect. The biomass and heavy metal extraction showed appropriate promoted effect in 1.5-2.5 V/cm, 100–150 h, whereas EHME continuous deceased and the decline rate relatively slow within 1.0V/cm, 100h. The result indicates the existence of optimization strategy, the best recommended strategy was T7 treatment, followed by T3, T8 and T12 treatments.DiscussionOverall, it is an acceptable option to study energy saving in terms of optimization of plant growth stage and electric field parameters, and provides novel perspectives for broadening the practical application.